Peculiarities of „social pedagogy” teaching methodics in pedagogic higher educational institutions with using interactive teaching methods - YAKOVLEVA, Valentyna; SAMARIN, Iliia (Journal of Education, Technology and Computer Science, 2013)
In this research paper it is exploring the need of providing interactive teaching methods into methodological complex of teaching activities of „Social pedagogy” subject for students getting „master” degree in specialty „Pedagogy of higher education” on the pedagogic faculty of National University of Life and Environmental Sciences. The problem of high dynamics of professional scientific knowledge amount growing is mentioned. Also there is an attempt to find the way of the problem solving by encouraging the using of modern, interactive teaching methods